Permeability Of Dentine. - Che Ghazali, Farid (2003)
This is an update on the present integrated knowledge regarding dentine permeability that assumed a role in dentine sensitivity and contribute clinically to the effective bonding properties of restorative dental materials. This paper will attempt to refer to in vivo and in vitro studies of dentine, permeability and the various interrelated factors governing it.